A technical solution to improve the red cab for touring in Chiang Mai: Chinese tourists' perspective - Miao Liu (2018)
© 2016 IEEE. Chiang Mai is the top tourist city in Thailand especially recently for Chinese tourists. Transport is a fundamental component of the tourism industry [1]. However, the most inconvenience of travelling in Chiang Mai for foreigners is that they have to use a local public transport that has no fixed routes and always requires a direct communication between the driver and tourists. Because of this, problems that might lead to an impedance of tourism development of the city can happen, for example, tourists can easily get lost by being dropped off at a wrong destination due to miscommunication. This paper focuses on proposing a technical solution to enhance the current local transportation to improve tourists' satisfaction from a technological perspective. An evaluation shows that the solution is considered to be a meaningful improvement of Chiang Mai public transport.